Magnetic interactions in compositionally modulated nanowire arrays. (23rd September 2016) - Palmero, Ester M; Béron, Fanny; Bran, Cristina; del Real, Rafael P; Vázquez, Manuel
Abstract: Series of high hexagonally ordered compositionally modulated nanowire arrays, with different Cu layer and FeCoCu segment thicknesses and a constant diameter of 35 nm, were fabricated by electroplating from a single electrolytic bath into anodic aluminum oxide membranes. The objective of the study was to determine the influence of ferromagnetic (FM) segment and non-ferromagnetic (NFM) layer thickness on the magnetic properties, particularly coercivity and magnetic interactions. First-order reversal curve (FORC) measurements and simulations were performed to quantify the effect of the inter-/intra-nanowire magnetostatic interactions on the coercivity and interaction field distributions. The FORC coercivity increases for a thick NFM layer and long FM segments due to decoupling of the the FM segments and the increased shape anisotropy, respectively. On the other hand, the interaction field presents a parallel strong reduction for a thick NFM layer and thin FM segments, which is ascribed to a similar NFM/FM thickness ratio and degree of FM segment decoupling along the nanowire.